The historical development of educational assessment in Chile: 1810–2014. Issue 1 (2nd January 2016) - Gysling, Jacqueline
Abstract : This article examines the historical development of the state's actions in educational assessment in Chile from the nineteenth century to the present day, based on the analysis of governmental decrees and regulations related to assessment, and their variability over time. The research identifies six distinctive periods, each of which expresses a different definition of assessment. In these six periods, the state consistently used assessment as a policy tool, hence this phenomenon is not a new or modern one. That much said, the use by the state of assessment has changed its mode of action and purpose. What is distinctive about the present is not only the way in which the state controls education through assessment by demanding the attainment of standards, but also its underlying educational programme which supports the systemic socialisation and economic integration of subjects, rather than their social socialisation and development as citizens.